Computed Tomography-guided Techniques for Localizing Pulmonary Nodules by Localization Needle versus Methylene Blue - Zhang, Hua; Kong, Jian; Guo, Jian-Xi (Current Medical Imaging, 2023)
Objective: The aim of this study was to evaluate the clinical value of computed tomographyguided localization needle (LN) and methylene blue (MB) for pulmonary nodule localization. Materials and Methods: Between November 2019 and January 2022, 547 patients underwent computed tomography-guided LN (n=171) or MB (n=376) localization and video-assisted thoracoscopic surgery (VATS) resection. Results: In total, 171 and 376 nodules were localized via LN and MB, respectively, with respective technical localization success rates of 92.98 % and 88.56 % (p = 0.111). The pulmonary nodule localization time was significantly shorter for the MB group than for the LN group (p < 0.05). However, the rates of total complication, chest pain, and cough were significantly lower in the LN group (χ 2 = 8.251/25.092/5.127, all p < 0.05). Furthermore, the LN group had a shorter VATS time than the MB group (p < 0.05). The VATS achieved a 100% operation success rate in both groups, and there was no significance between groups with respect to the types of surgery (p > 0.05) or the blood loss (p > 0.05). Moreover, logistic regression analysis showed that the localization technique was an independent risk factor for total complications and chest pain. Conclusion: Both techniques can effectively localize pulmonary nodules before VATS. MB had a shorter localization time, but the LN had a shorter VATS time and a lower incidence of complications, especially chest pain.
Keywords: Computed tomography